Les usages de la métalepse d’auteur dans Partonopeu de Blois et Le Bel Inconnu - Nathalie Leclercq (Perspectives Médiévales)
This article will investigate the extent to which the use of authorial metalepsis, theorized by Gérard Genette, highlights, in Le Roman de Partonopeu de Blois and Le Bel Inconnu, the functions of a participatory author whose active involvement reveals his desire to claim his freedom of invention. When both auhtors compare themselves to their characters, they are indeed drawing attention to their own experience of love by asking the reader to become aware of both their presence and their power. Furthermore, the authorial metalepsis, which destabilizes the boundaries between reality and fiction, generates a crystallization of the author-subject and offers the possibility for authors to assert their control over their creation. Moreover, it allows the reader/listener to be associated with the act of narration by establishing a connivance that creates a reader’s metalepsis.